Factors influence university student to take Multi-Level Marketing (MLM) as career choice - Lai, Wei Shen (2023)
This research delves into the factors influencing university students in Malaysia as they consider Multi-Level Marketing (MLM) careers. The study centres on key variables, including Income, Perception of Salespeople, Self-Efficacy, and Perception of Company. Set against the backdrop of Malaysia's regulatory environment, governed by the Direct Selling Association, the research incorporates theoretical lenses like Maslow's Hierarchy of Needs and career decision-making self-efficacy. Grounded in the distinctive features of the Malaysian MLM market, the investigation aspires to provide nuanced insights for academia, policymakers, and industry stakeholders. The anticipated outcomes aim to illuminate the motivations steering students toward MLM professions, contributing to a comprehensive understanding of the factors shaping career decisions among university students in Malaysia. This research seeks to bridge gaps in existing literature and offer practical implications for stakeholders in the MLM industry.